A commercially available siderophore-receptor and porin-based vaccine reduced the prevalence of Escherichia coli O157:H7 in the feces of beef cattle under field conditions in 10 commercial feedlots. - Butler, Brooks A. (Kansas State University, 2012)
A total of 284,300 animals from 10 commercial feedyards in Nebraska and Colorado were used to evaluate the effectiveness of a siderophore-receptor/porin protein-based vaccine under commercial feedlot conditions. Individual feedlots were assigned to 1 of 2 treatments: 1) all incoming cattle injected with 2 ml of SRP E. coli O157:H7 vaccine subcutaneously at arrival and at time of re-implant (VAC) or 2) all incoming cattle were not vaccinated, and were used as negative controls (CON). Twenty freshly voided fecal samples were taken from 5 pen floors of market ready cattle at each feedyard once a month during May, June, July, and August of 2010. Pre-harvest blood samples were collected on 3 occasions throughout the summer (June, July, and August). For each sampling month, 1 lot of 5 animals representing each feedyard was sampled. Fecal and blood samples were shipped to Epitopix, LLC for subsequent microbiology and anti-SRP antibody testing. Samples were coded such that laboratory personnel were blinded to the location and treatment of samples. Cattle receiving VAC treatment had reduced prevalence of E.coli O157:H7 in their feces relative to the E. coli O157:H7 prevalence in the feces of CON cattle (12.83% vs. 20.25% for VAC and CON, respectively; P = 0.07). Anti-SRP antibody titer was higher in the serum from VAC cattle relative to the SRP titer levels in serum obtained from CON cattle (0.622 and 0.075 for VAC and CON, respectively; P < 0.001). These data suggest that vaccination of feedlot cattle with SRP upon arrival at the feedlot and again 70-100 days pre-harvest reduces shedding of E. coli O157:H7.
Keywords: E. coli O157; Cattle; Veterinary Medicine (0778)